STUDY OF DIFFERENCES IN PLANTING TIME ON YIELD OF PEANUT BY INTERCROPPING WITH THE SORGHUM PLANTING MODEL IN DRY LAND - Widiastuti E. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Peanut is one of the potential legumes used in intercropping systems. Peanut cultivation in intercropping is often depressed due to competition with other plants which reduces yield; therefore intercropping of peanuts with sorghum must be carried out properly. One way to minimize competition in the intercropping system is arranging planting time. Aim of this study is to determine growth and yield of peanuts at different planting times in the intercropping with sorghum at many planting models in dry land. The experiment has been carried out at the Pringgabaya Agricultural Technology Research and Assessment Installation (IP2TP) East Lombok, September 2020 – January 2021. Split Plot design was used with three peanut planting times (as the main plot) which are 14 days before sorghum, same planting time with sorghum, and 14 days after sorghum. Sorghum planting model (as subplot): single row (70 cm x 20 cm spacing) 1 plant per clump, double row 20 cm x (50 cm – 100 cm) spacing 1 plant per clump, double row spacing 40 cm x (40 cm – 100 cm) 2 plants per clump. The highest peanut yield 1.69 t/ha, obtained when peanuts planted 14 days before sorghum with a double row sorghum planting model with a spacing of 40 cm x (40 cm – 100 cm) 2 plants per clump (1.69 t/ha). This can be recommended for peanut-sorghum intercropping systems in. dry land.